A Detailed Review on Acne vulgaris - Kadam, T. V.; Darekar, A. B. (Novel Aspects on Pharmaceutical Research Vol. 2, 2023)
This study focuses on the causes and treatments options for acne vulgaris. The most well-known pilosebaceous follicle skin condition, acne vulgaris is characterized by papules, knobs, growths, comedones, pustules, and regular scars that are primarily dispersed on the face, middle, and upper back. Inflammation of pimples is a common skin condition that affects people of all ages. The gram-positive anaerobic microorganism Propionibacterium acnes, which is regarded as discharge-framing microorganisms, causes inflammation of the skin. For the treatment of inflammation of the skin, several restorative plant parts and dermatological drugs are used. The mainstay of treatment for topical specialists includes benzoyl peroxide, anti-infection medications, retinoid, and others; they may be administered in combination. Systemic treatment, which includes isotretinoin, hormonal therapy, and oral anti-microbials, must be chosen based on the needs of the patient. Photographic assistance is also helpful for them when receiving physical therapy for a certain sort of injury evacuation. They eventually run into treating dermatologists because there are numerous traditional and cutting-edge topical and systemic experts available to treat acne vulgaris.